Preoperative application of carbon nanoparticles in transoral endoscopic thyroidectomy vestibular approach for papillary thyroid cancer - Wang, Yonghui; Zhang, Li; Huang, Jinning; Wang, Liquan (Frontiers in Oncology, 2023)
Background Carbon nanoparticles (CNs) has been widely used in the protection of parathyroid gland and acted as the tracer agent in the central lymph node dissection. However, the right time of injection of CNs has not been well illustrated in the Transoral endoscopic thyroidectomy vestibular approach (TOETVA). The purpose of this study was to evaluate the safety and feasibility of preoperative injection of CNs in TOETVA for papillary thyroid cancer. Methods From October 2021 to October 2022, a total of 53 consecutive patients with PTC were retrospectively analyzed. All patients underwent unilateral thyroidectomy via TOETVA. The patients were divided into the preoperative group (n=28) and intraoperative group (n=25) by the injecting time of the CNs. In the preoperative group, 0.2mL of CNs was injected into the thyroid lobules with malignant nodules 1 h before surgery. The numbers of total central lymph node (CLN )and metastatic central lymph node (CLNM), parathyroid auto-transplantation, accidental removal of parathyroid, parathyroid hormone level was recorded and analyzed. Results The leakage of CNs happened more frequently in the intraoperative group compared to the preoperative group (P=0.002). The mean number of retrieved CLN was similar in the preoperative group and intraoperative group, as was the mean number of CLNM. In the parathyroid protection, more parathyroid was discovered in the preoperative group compared to the intraoperative group (1.57±0.54 vs 1.47±0.50, P=0.002), and less parathyroid auto-transplantation (P=0.004) and accidental removal of parathyroid (P=0.036) in the preoperative group. However, the PTH level between the two group was similar after the 1st day and 1st month. Conclusion The preoperative injection of CNs is a safe and effective method to protect the parathyroid glands (PGs) for patients with PTC undergoing TOETVA. However, the value of preoperative injection of CNs in TOETVA for central lymph node dissection needs to be further studied.